2011
DOI: 10.1007/s11060-011-0562-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin and survival in glioblastoma multiforme

Abstract: Serum albumin is an established predictor of survival in numerous cancers but its prognostic value in central nervous system tumours has not been established. Here we have examined prognostic factors in 685 patients with histologically proven glioblastoma multiforme (GBM), the majority of which (n = 549) had pre-operative serum albumin assayed. Mean serum albumin was 34.7 g/l (SD 5.2). Post-operative survival was significantly less for patients with hypoalbuminaemia (<30 g/l, n = 82) than for patients with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Schwartzbaum et al found that preoperative hypoalbuminemia (<3.4 g/dL) was associated with a marked reduction in median survival from 494 to 62 days in 24 GBM patients . Several subsequent studies also identified preoperative serum albumin as a survival predictor for GBM . In our retrospective review, lower long‐term serum albumin level was independently associated with shorter survival after adjustment for the significant confounders.…”
Section: Discussionmentioning
confidence: 52%
“…Schwartzbaum et al found that preoperative hypoalbuminemia (<3.4 g/dL) was associated with a marked reduction in median survival from 494 to 62 days in 24 GBM patients . Several subsequent studies also identified preoperative serum albumin as a survival predictor for GBM . In our retrospective review, lower long‐term serum albumin level was independently associated with shorter survival after adjustment for the significant confounders.…”
Section: Discussionmentioning
confidence: 52%
“…Preoperative serum albumin levels have been recognized as prognostic in glioblastomas [8,9]. However, this prognostic effect should be re-examined in the era of standard therapy [1], when molecular markers such as MGMT promoter methylation status are taken into consideration [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory conditions, high serum IGFBP-2 levels are associated with elevated cytokine interleukin (IL)-6 [22,24-26], another prognostic factor for glioblastoma [9,27] that negatively regulates serum albumin level by increasing catabolism and down-regulating hepatic synthesis, which further worsens the nutritional status of the patient. Therefore, during glioblastoma-induced inflammatory responses, the interaction among albumin, IGFBP-2 and IL-6 may greatly affect clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, nutritional status and in ammation could re ect survival outcomes in high-grade gliomas 5 . Serum albumin level has been found to be an independent prognostic factor for survival, and lower albumin levels correlated with poor prognosis in patients with GBM [14][15][16] . Recent studies also showed the PNI to be an independent prognostic factor for survival in GBM [17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%